Strategi Digital Marketing dan Customer Engagement Dalam Meningkatkan Kinerja UMKM Kuliner Di Kota Manado - Lidya Djuwita Pratiwi Canon; Injilia Wulan Gratia Wua; Sherly Ernawaty Susanto (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the effect of digital marketing strategies and customer engagement on the business performance of culinary MSMEs (Micro, Small, and Medium Enterprises) in Manado City. The rapid growth of digital technology has transformed the way small businesses promote their products and interact with customers. Using a quantitative approach with survey methods, data were collected from 120 culinary MSME owners in Manado City through purposive sampling. Multiple linear regression analysis was employed to test the research hypotheses. The results show that digital marketing strategy has a significant positive effect on MSME business performance (β = 0.412, t = 5.214, p < 0.05), and customer engagement also has a significant positive effect on MSME business performance (β = 0.387, t = 4.893, p < 0.05). Simultaneously, both variables explain 68.3% of the variance in MSME performance (R² = 0.683). This study contributes novelty by integrating the Digital Marketing Mix framework with the Customer Engagement theory in the context of culinary MSMEs in Eastern Indonesia, specifically Manado City, which has not been extensively studied in prior literature.